AB1198 IL-18 is a hallmark of juvenile dermatomyositis-associated interstitial pneumonia. (23rd January 2014) - Takezaki, S.; Yamazaki, Y.; Okura, Y.; Yamada, M.; Kobayashi, I.; Ariga, T.
Abstract : Background: Dermatomyositis (DM) is an inflammatory disease characterized by weakness in the proximal muscles and pathognomonic skin rash. Although interstitial lung disease (ILD) is a common complication of DM [1] and makes poor prognosis, the etiology of ILD developing in DM (JDM) cases was still unknown. Recent report has demonstrated that serum interleukin (IL)-18 levels are significantly higher in adult patients with DM-associated ILD than those without ILD [2]. On the other hand, complication of ILD is rare and not well characterized in JDM. Objectives: To evaluate the clinical significance of serum IL-18 levels and other JDM-associated markers in JDM cases with or without ILD. Methods: 13 JDM patients, 5 with ILD (ILD+) and 8 without ILD (ILD-) followed-up at Hokkaido University Hospital from 1990 to 2008 were enrolled. Sex ratio and the age of onset were not significantly different between both groups. The samples were obtained at diagnosis and remission after treatment. Serum IL-18 levels were measured by Human IL-18 ELISA kit (BML, Nagoya, Japan). Serum neopterin, ferritin and soluble (s) IL-2 receptor (R) levels were also measured. Statistical analyses were performed by Mann-Whitney's U test and Pearson product-moment correlation coefficient. Results: Serum IL-18 levels at diagnosis were significantly higher (p<0.01) in ILD (+) cases than in ILD (-) cases. Serum levels of neopterin, ferritin and sIL-2R were not significantly different between both groups. No correlation among the tested makers was observed. All of the tested markers were significantly decreased at the inactive phase in both groups. Conclusions: In JDM-ILD, serum IL-18 levels were significantly high in active phase and decreased with remission, suggesting involvement of innate immunity, particularly of macrophages, in the pathogenesis of ILD. On the other hand, serum levels of neopterin, ferritin and sIL-2R could be affected by the disease severity of JDM itself or other complication such as hemophagocytic syndrome. References: Feldman BM, Rider LG, Reed AM, Pachman LM. Juvenile dermatomyositis and other idiopathic inflammatory myopathies of childhood. Lancet. 2008 Jun 28;371(9631):2201-12. Gono T, Kawaguchi Y, Sugiura T, Ichida H, Takagi K, Katsumata Y, Hanaoka M, Okamoto Y, Ota Y, Yamanaka H. Interleukin-18 is a key mediator in dermatomyositis: potential contribution to development of interstitial lung disease. Rheumatology (Oxford). 2010 Oct;49(10):1878-81. Disclosure of Interest: None Declared